Saponins: properties, applications and health benefits - Koh, Rani; Tay, Isaac (Nova Science Publishers, 2012)
Saponins : structural diversity, properties, and applications / Ben A. Chindo, Bulus Adzu, Karniyus S. Gamaniel -- Saponins from Panax species : chemistry, isolation, and analysis / Jian-Bo Wan ... [et al.] -- Triterpenoid saponins from genus Gypsophila L. (Caryophyllaceae) / Yotova, I. Krasteva, S. Nikolov -- Potential of triterpenoids from ginseng (Panax quinquefolius and Panax ginseng C.A. Meyer) to regulate cultured adipocytes / Chia-Rou Yeo, David G. Popovich -- Saponin use as antimicrobial in fibrous and consumer products / Vivechana Diixit, S. Kay Obendorf -- Evidence of bioactivity from Ganoderma lucidum triterpenoids in cultured cell models / Weimei Ruan, David G. Popovich -- Recent developments of soyasaponins from soy (Glycine max (L.)) bioactivity in cell models / Wei Zhang, David G. Popovich
"Nova biomedical. - Includes bibliographical references and index. - Electronic reproduction; Palo Alto, Calif; ebrary; 2013; Available via World Wide Web; Access may be limited to ebrary affiliated libraries